(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Neuregulin-4 is a cytokine with many functions and is primarily produced by fat tissue. AIM OF THE STUDY The aim of the study was to observe the relationship between serum neuregulin-4 levels and diabetes regulation in type 2 diabetes mellitus (T2DM), and to compare neuregulin-4 levels of diabetic subjects with those in healthy controls. METHODS Patients with T2DM were included to the study. Healthy subjects were enrolled as controls. Subjects with T2DM with glycated haemoglobin (HbA1c) <7% were classed as well controlled and those with HbA1c ≥7% were classed as poorly controlled. Neuregulin-4 levels of the study and control groups were compared. RESULTS The neuregulin-4 levels of the poorly controlled T2DM, well-controlled T2DM and control groups were significantly different (p = 0.005). Neuregulin-4 was significantly correlated with fasting plasma glucose (r = 0.247, p = 0.002) but not with HbA1c. In a regression analysis model, 0.1 point elevation in neuregulin-4 levels increased the rate of existence of T2DM 4.4-fold (odds ratio 4.4, 95% confidence interval 1.26–15.1; p = 0.02). CONCLUSION Neuregulin-4 is significantly increased in patients with T2DM compared with control subjects, which means that it could be a marker of T2DM. Since neuregulin-4 was correlated with fasting glucose, we suggest that elevated neuregulin-4 could predict poor control in T2DM for short periods when HbA1c is not useful. Moreover, one unit elevation in neuregulin-4 (0.1 ng/ml) increases the rate of existence of T2DM 4.4-fold, independently from other variables.